Математическое моделирование поверхности арочных зубьев с эллиптической продольной формой - Кириченко, А. Ф.; Матюшенко, Николай Васильевич (НТУ "ХПИ", 2004)
В даній статті отримано математичну модель поверхні зубів циліндричних передач Новікова ДЛЗ з еліптичною подовжньою формою, що нарізані різцевою головкою.

The mathematical model tooth geometry of gears are studied. An equation of the ellips-arc tooth’s surface of Novikov’s cylindrical gearing with two action lines is found in the present note by the duplex spread blade method.
Keywords: зубчатые передачи; механизмы; локально-кинематические свойства; прочность; зацепление